'As a Mass, a Phenomenon so Hideous'1: Crowd Psychology, Impressionism, and Ford Madox Ford's Propaganda. (1st May 2013) - Doty, Benjamin
<x xml:space="preserve">Abstract</x> Ford Madox Ford was an unusual choice in the British government's stable of literary authors serving as propagandists during the First World War. Beginning with an analysis of the 1914 'Declaration by Authors' in support of the First World War, this article moves on to explicate Ford's own style—especially as it is explained in 'On Impressionism'—and read it in opposition to the 'Declaration'. His use of the highly individualistic and idiosyncratic technique of literary impressionism produced works radically different from the prevailing propagandistic style, which, taking advantage of advances in crowd psychology, emphasized unanimity and shaping readers into a crowd. Ford's writings, and primarily Between St. Dennis and St. George, actively work against this tendency, rectifying the seeming contradiction between impressionism and propaganda by forging a new form of propaganda. This radical critique of the existing style was Ford's way of extricating himself from the wartime effacement of the individual in favour of a national mass.